1986
DOI: 10.1002/eji.1830160211
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of immune complexes from lymphocytes to follicular dendritic cells

Abstract: Antigens in the form of immune complexes are retained on the membranes of follicular dendritic cells (FDC) for long periods of time. To examine how immune complexes reach germinal centers, where FDC are located, we injected mice with anti-2,4-dinitrophenyl (DNP) antibodies complexed to DNP-myoglobin-coated gold particles. The distribution of the particles in spleens or draining lymph nodes was then determined with the electron microscope. The vast majority of the particles were cell bound. Shortly after inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Our current data and recent results by Tenner-Racz and colleagues (31) FDC expression of PGIS is more evidence supporting the view that FDC originates from local fibroblast as reviewed by Heinen and Bosseloir (34). Ultrastructural (35,36), enzymological (35,37), and functional studies (38,39) support this view. We demonstrated recently that fibroblasts as well as FDCs express 3C8 Ag (25).…”
Section: Discussionsupporting
confidence: 89%
“…Our current data and recent results by Tenner-Racz and colleagues (31) FDC expression of PGIS is more evidence supporting the view that FDC originates from local fibroblast as reviewed by Heinen and Bosseloir (34). Ultrastructural (35,36), enzymological (35,37), and functional studies (38,39) support this view. We demonstrated recently that fibroblasts as well as FDCs express 3C8 Ag (25).…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have reported that Ag transport and retention on FDCs require the formation of ICs (9,(19)(20)(21). Protein Ag is not detected on FDCs in the absence of specific Abs.…”
Section: Discussionmentioning
confidence: 99%
“…They either require the formation of ICs (5, 7-9, 12, 18, 19) or the presence of larger numbers of transgenic cognate B cells (14)(15)(16)(17). In particular, retention of model protein Ags on FDCs was only observed to occur efficiently when Ag-specific Abs were present (5,7,9,(19)(20)(21). These conditions simulate the situation during a secondary immune response.…”
mentioning
confidence: 99%
“…Alternatively, noncognate B cells, which also can capture and transport Ag in the follicle, could potentially display Ag to GC B cells in the absence of FDC, providing a partial redundancy for the Ag-trapping role of FDC. The collapse of the GC in FDC-less mice at day 12 may reflect turnover of these particular B cells (5,41,42).…”
Section: Discussionmentioning
confidence: 99%